2020
DOI: 10.1016/j.clinre.2019.06.010
|View full text |Cite
|
Sign up to set email alerts
|

HBV vaccination with Fendrix is effective and safe in pre-dialysis CKD population

Abstract: Background: Patients with chronic kidney disease have a poor response to hepatitis B vaccine due to the immunodeficiency conferred from chronic uremia. A recombinant HB vaccine containing an improved adjuvant system AS04 (HBV-AS04) has been manufactured but scarce evidence exists on HBV-AS04 use among patients with CKD. Aim: To assess efficacy and safety of an adjuvanted recombinant vaccine (HBV-AS04) in a large cohort of CKD patients at pre-dialysis stage (with susceptibility to HBV infection). Methods: Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Ahmadi found that there was no significant difference in achieving seroprotection between four doses of a 40 µg compared to three doses of a 20 µg of the Euvax B [ 21 ]. Alternative formulations have also been investigated, including one reviewed by Fabrizi, who looked at the effectiveness of Fendrix, a recombinant HBV vaccine with an improved adjuvant system, and found promising results [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmadi found that there was no significant difference in achieving seroprotection between four doses of a 40 µg compared to three doses of a 20 µg of the Euvax B [ 21 ]. Alternative formulations have also been investigated, including one reviewed by Fabrizi, who looked at the effectiveness of Fendrix, a recombinant HBV vaccine with an improved adjuvant system, and found promising results [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen years after vaccination, the team tested all subjects for antibodies that would protect them from infection and found that the number of antibodies against the virus had fallen since vaccination. The factors associated with a greater likelihood of continuing to present high antibody levels at 15 years were: being male, being older at the time of vaccination and having developed a high number of antibodies at the start [8][9][10][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Scientific Background and Rationalementioning
confidence: 99%
“…A literature review indicated that the mean percentage of workers who do not respond to the Fendrix Ò vaccine ranges from below 1% to 10% [7,15,19,29,32,35]. This would noticeably affect sample size calculation.…”
Section: Sample Sizementioning
confidence: 99%
“…Compound 20 (11 mg, mmol) was stirred in a solution of 4 N HCl in dioxane for 1 h. The solvent was then removed to obtain compound 21 in quantitative yield as hydrochloride salt (gray solid). 1 N-(4-Chloro-2,5-dimethoxyphenyl)-4-phenoxybenzenesulfonamide (22). Compound 22 was synthesized using 4-chloro-2,5-dimethoxyaniline (2a, 140 mg, 0.74 mmol) and 4-phenoxybenzenesulfonyl chloride (3j, 100 mg, 0.37 mmol) as light yellow solid (51 mg, yield = 33%).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Similarly, combination adjuvants can be obtained using a PRR or NLR ligand, an immunogenic protein, a delivery system, or another adjuvant with a complementary mechanism of action . One such combination AS04 (adjuvant system 04), consisting of MPLA and alum, has been FDA approved in a hepatitis B vaccine Fendrix and human papillomavirus vaccine Cervarix. Alternative combinations involving approved adjuvants, TLR agonists, NOD agonists, and delivery systems are being explored. …”
Section: Introductionmentioning
confidence: 99%